Evaluasi Kerangka Hukum Penanganan Pandemi Covid-19 dalam Perspektif Hukum Tata Negara Darurat (Evaluation of the Legal Framework for Handling the Covid-19 Pandemic in the Perspective of Emergency Constitutional Law) - Novianto Murti Hantoro (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2021)
The handling of the Covid-19 pandemic has been going on for more than a year. The Covid-19 pandemic is being handled within various legal frameworks by several countries. This article evaluates the legal framework from the perspective of emergency constitutional law by discussing the legal framework used and evaluating its advantages and disadvantages. The aim is to contribute ideas to the discipline of emergency constitutional law and to evaluate the legal framework. The writing of this article uses normative legal research methods and qualitative analysis through juridical and comparative analysis. Basedon the results of the analysis, Indonesia is in the category of observing existing laws in handling the Covid-19 pandemic. The enforcement of existing law as an emergency measure is not the same as enforcing emergency constitutional law, because there are elements that are not fulfilled, for example until when the law remains in force. When compared the two of enforcing the existing laws and drafting a new law specifically for handling the Covid 19 pandemic, there are advantages and disadvantages. The advantages of enforcing the existing laws will be the disadvantages of drafting a new law and vice versa. One of them, with the new law, the handling will be more focused than enforcing the three existing laws with different leading sectors. The current legal framework for handling the Covid-19 pandemic has weaknesses, but it has not failed. If the situation returns to normal, the emergency decrees and several related regulations need to be revoked. AbstrakPenanganan pandemi Covid-19 sudah berlangsung lebih dari satu tahun. Pandemi Covid-19 ditangani dengan kerangka hukum beragam oleh beberapa negara. Artikel ini mengevaluasi kerangka hukum tersebut dari perspektif hukum tata negara darurat dengan membahas kerangka hukum yang digunakan serta evaluasi terhadapkelebihan dan kekurangannya. Tujuannya untuk memberikan sumbangan pemikiran terhadap ilmu hukum tata negara darurat dan mengevaluasi kerangka hukum tersebut. Penulisan artikel ini menggunakan metode penelitian hukum normatif dan analisis kualitatif melalui analisis yuridis dan perbandingan. Berdasarkan hasilanalisis, Indonesia masuk dalam kategori menggunakan undang-undang yang ada (existing law) dalam penanganan pandemi Covid-19. Penggunaan existing law sebagai tindakan darurat tidak sama dengan menerapkan hukum tata negara darurat, karena terdapat unsur yang tidak terpenuhi, misalnya kapan penggunaan undang-undang tersebut akan berakhir. Apabila dibandingkan antara penggunaan existing law dan membentuk undang-undang baru khusus untuk penanganan pandemi Covid 19, terdapat kelebihan dan kekurangan. Kelebihan penggunaan existing law akan menjadi kekurangan pembentukan undang-undang baru, dan sebaliknya. Salah satunya, dengan undang-undang baru, penanganan akan lebih fokus dibandingkan dengan menggunakan tiga undang-undangyang ada dengan leading sector yang berbeda. Kerangka hukum penanganan pandemi Covid-19 saat ini memiliki kelemahan, namun tidak gagal. Apabila situasi kembali normal, penetapan kedaruratan dan beberapa aturan terkait perlu dicabut.